SURVEI TINGKAT KESEGARAN JASMANI SISWA KELAS XI (SEBELAS) SMA MUHAMMADIYAH 1 BABAT KABUPATEN LAMONGAN - NURCAHYO, EKO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Students’ physical fitness was the important things should be kept. To keep physical fitness, students were required to have sport regularly and have a good meal in quality and quantity side. So that, students   would have high students’ grade physical fitness and used their mind and energy to act in the school. To know whether students’ grade physical fitness are in standard level, so that it was required a test which  is used Indonesian Physical Fitness Test.The objective of this research was knowing whether students’ grade physical fitness Eleventh Grade of Senior High School of  Muhammadiyah 1 Babat, Lamongan Regency. This research used survey for the methodology. This research took location on Senior High School of  Muhammadiyah Babat, Lamongan Regency. The population of this research were all the students of XI class which was consisted by 176 students. Techniques of taking the sample  was used cluster sampling. The sample of this research was the students of XI IPS 2 which the amounts are 29. They were consisted by 15 male students and 14 female students. That sample was taken in a age range from 16 to 19 years old. The data was taken by Indonesian Physical Fitness Test. The result of the research showed that the male students who had percentage 67% which students’ grade physical fitness were good, 33% which students’ grade physical fitness were in between. While female students who had percentage 50% which students’ grade physical fitness were good, 36% which students’ grade physical fitness were in between, 14% which students’ grade physical fitness were low. Key words: Survey, Students’ Grade Physical Fitness